MUSEUM WARISAN BUDAYA DAYAK TAK BENDA KALIMANTAN TENGAH DI PALANGKA RAYA - Ovianty, Oktantri Eka; Hamidah, Noor Hamidah; Usop, Tari Budayanti (Fakultas Teknik Universitas Palangka Raya, 2026)
Museum as a place to store historical objects both tangible and intangible. Intangible cultural heritage in Central Kalimantan Province includes: karungut, tiwah, handep, sapundu, Sasana Bandar, Mamapas Lewu, Nahunan, Wadian Dadas, Babukung, Nota Garung, Bana'I Tamu, Wadi, Penggolaran, Manugal, and Handap requires space in the Museum. The goal is to design a Cultural Heritage Museum that can accommodate various activities related to the Intangible Dayak cultural heritage of Central Kalimantan with a contextual architecture approach. The design method used is qualitative based on a contextual approach. Contextual architecture is a relationship that has a harmonious meaning, is unified, and has an interest that is visually related to a sustainable environment. Contextual application includes the processing of space, circulation, appearance, and supporting facilities. Contextual is described through the implementation of a space for tradition and oral expression, a performing arts space, a traditional and ritual space, a space for natural and life knowledge, a cultural study, a traditional music studio.